Knowledge, attitude and practice towards general waste management among housewives: evidence from urban slums of Delhi - Anshu Tomar; Ayushi Rana; Bhawna; Neha Dagar (International Journal Of Community Medicine And Public Health, 2026)
Background: Waste that cannot be recycled and generated in households and factories or companies, also named as residual waste is called general waste. Materials such as non-recyclable plastic, polythene, kitchen wraps and packing papers are few examples of general waste. The process of collection, treatment, recycle and disposal of different waste materials is waste management. Household waste management can be effectively done if housewives have adequate knowledge, a positive attitude and adopt healthy practices. Methods: A quantitative research approach was used for this study. The research was conducted in urban slum area, Aali Gaon of New Delhi among 100 using purposive sampling. The tools used were structured knowledge questionnaire, 5- point Likert attitude scale and structured practice checklist. Results: The findings showed that 55% of housewives had average knowledge, 56% of housewives had unsatisfactory practice level, whereas in attitude score, 67% housewives had positive attitude level. A significant association was found knowledge and attitude with demographic variables. Conclusions: Thus, there is a need for mass health education amongst the housewives by which knowledge and practice can be enhanced.